Viral Strain-Specific Activation of Pathogen-Associated Molecular Pattern-Triggered Immunity Enhances Symptom Severity in Broad Bean Wilt Virus 2 Infection - Han, Soo-Jung; Choi, Boram; Kim, Myung-Hwi; Kwon, Sun-Jung; Kwak, Hae-Ryun; Seo, Jang-Kyun (Frontiers in Plant Science, 2021)
Broad bean wilt virus 2 (BBWV2) is an emerging virus in various economically important crops, especially pepper (Capsicum annuum L.), worldwide. Recently, the emergence of various BBWV2 strains that induce severe symptoms has increased damage to pepper crops. While the symptomatic variations among virus strains should be associated with differences in the transcriptomic reprogramming of host plants upon infection, underlying molecular mechanisms and associated genes are largely unknown. In the present study, we employed transcriptome analysis to identify responsible host factors for symptom enhancement in the BBWV2-pepper pathosystem using two distinct BBWV2 strains, PAP1 (a severe strain) and RP1 (a mild strain). Comparative analysis of the differentially expressed genes revealed that various genes associated with pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) and ethylene signaling were significantly up-regulated upon infection with the severe PAP1 strain, but not with the mild RP1 strain. Indeed, hormone analysis revealed that ethylene emission was significantly increased in pepper plants infected with PAP1. These observations imply that the activation of the PTI-associated defense responses reinforce symptom formation during BBWV2 infection in a virus strain-specific manner.